KUSWATA KARTAWINATA (1936–2024), INDONESIA’S BOTANIST AND ECOLOGIST: A BRILLIANT CAREER SUPPORTING SCIENCE AND CONSERVATION, BRIDGING TWO CENTURIES IN THE WORLD’S GREATEST TROPICAL ARCHIPELAGO - Wong, Khoon Meng (Research Center for Biology, 2024)
Dr. Kuswata Kartawinata (1936–2024) was a prominent Indonesian botanist and ecologist whose remarkable career spanned over five decades, contributing significantly to plant taxonomy, forest ecology, and biodiversity conservation. He held pivotal roles in institutions such as the Herbarium Bogoriense, UNESCO, and CIFOR. He also spearheaded various international initiatives on tropical forest management and conservation. Kuswata’s work included extensive research, teaching, and mentoring, with a legacy of over 186 publications and countless supervised theses. His contributions bridged scientific rigor and practical conservation strategies, leaving an enduring impact on tropical ecology in Indonesia and beyond. His unwavering dedication to science and mentorship inspired generations of botanists and ecologists globally.